Complete mitochondrial genome sequence of flathead fish Platycephalus sp.1 (Scorpaeniformes: Platycephalidae). Issue 1 (2nd January 2019) - Luo, Xiaodong; Li, Qiu; Wang, Zhiyang; Xiao, Jiaguang; Yang, Tianyan; Gao, Tianxiang; Wang, Xihong
Abstract: In this study, the complete mitochondrial genome (mitogenome) sequence of Platycephalus sp.1 was sequenced by long polymerase chain (PCR) reaction and primer walking method. The mitogenome was total 16552 base pairs (bp) in length and contained 2 ribosomal RNA (rRNA), 13 protein-coding genes (PCGs), 22 transfer RNA (tRNA), and 1 non-coding region (control region) as those found in other vertebrates. The overall base composition was displayed as 25.8% T, 30.0% C, 27.0% A, and 17.2% G. The neighbour-joining tree was reconstructed based on the 13 PCGs sequences of Platycephalus sp.1 and other six species. The mitogenome data would provide useful information for further studies on the taxonomy and phylogenetic analysis of Platycephalidae.